2010
DOI: 10.1111/j.1743-6109.2010.01871.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Desire and the Female Sexual Function Index (FSFI): A Sexual Desire Cutpoint for Clinical Interpretation of the FSFI in Women with and without Hypoactive Sexual Desire Disorder

Abstract: Introduction A validated cutpoint for the total Female Sexual Function Index scale score exists to classify women with and without sexual dysfunction. However, there is no sexual desire (SD) domain-specific cutpoint for assessing the presence of diminished desire in women with or without a sexual desire problem. Aims This article defines and validates a specific cutpoint on the SD domain for differentiating women with and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 123 publications
(84 citation statements)
references
References 22 publications
4
77
0
3
Order By: Relevance
“…15,16 Finally, the desire score for HSDD cases in the present study (3.0 -1.3) was well below the recently established FSFI sexual desire clinical cutoff point of 5.0. 27 …”
Section: Discussionmentioning
confidence: 99%
“…15,16 Finally, the desire score for HSDD cases in the present study (3.0 -1.3) was well below the recently established FSFI sexual desire clinical cutoff point of 5.0. 27 …”
Section: Discussionmentioning
confidence: 99%
“…26,27 In addition, we have recently shown that a cut point of 5 or less on the sexual desire domain can be used to differentiate women with and without symptoms of HSDD. 24 …”
Section: Data Collection and Sourcesmentioning
confidence: 99%
“…25 The FSFI desire domain score was similarly well below the recently validated cut point of 5.0, again indicating diminished sexual functioning. 24 Current diagnosis of the medical condition as assessed by clinician medical history review. Only conditions that are reported for 5% or more of participants are itemized; others are also included in the total when categorizing women with four or more current medical conditions.…”
Section: Quality Of Life Relationship Satisfaction and Sexual Functionmentioning
confidence: 99%
“…Scores were derived for adolescents who reported partnered sexual activity within the prior 4-week period and at least one past occasion of oral, vaginal, or anal sex. For the predictive analyses, female respondents were classified as having had a persistent sexual problem at any given assessment if they reported: a score of 5 on the desire domain or a total FSFI score of 26.55 as these are the only domains with validated cutoff scores [27,28]. For descriptive purposes, scores below the midpoint on the remaining domains indicate low sexual functioning (i.e., at least half the time, no/low desire or arousal, difficulty to extreme difficulty, moderate to high dissatisfaction, high to very high pain, or no/low confidence in functioning).…”
Section: Methodsmentioning
confidence: 99%